2018
DOI: 10.1136/archdischild-2017-314628
|View full text |Cite
|
Sign up to set email alerts
|

Maternal weight and infections in early childhood: a cohort study

Abstract: We observed an association between overweight and obesity during pregnancy, and hospitalisations for infectious diseases during early childhood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 22 publications
1
26
0
Order By: Relevance
“…Moreover, this study only captures the most severe cases of infection that require hospitalisation; it will underestimate rates of all infections in this population as we did not have access to data for primary care settings, where the majority of childhood infections will be managed. Additionally, we were unable to adjust for the following factors: maternal antibiotic use in pregnancy and underlying maternal conditions, which may have contributed to preterm labour and potentially the long term health of the child [ 40 ]; maternal smoking, which is a risk factor for both IUGR [ 41 ] and childhood respiratory infections in childhood [ 42 ]; maternal BMI which may increase the risk of childhood infections [ 43 ]; or explore the potentially mediating effect of breastfeeding, which is known to be protective against certain infections during early childhood [ 7 , 8 ]. Finally, we only included births occurring in NHS hospitals as births occurring in private or military hospitals or at home were excluded due to poor linkage rates with hospital admission records.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, this study only captures the most severe cases of infection that require hospitalisation; it will underestimate rates of all infections in this population as we did not have access to data for primary care settings, where the majority of childhood infections will be managed. Additionally, we were unable to adjust for the following factors: maternal antibiotic use in pregnancy and underlying maternal conditions, which may have contributed to preterm labour and potentially the long term health of the child [ 40 ]; maternal smoking, which is a risk factor for both IUGR [ 41 ] and childhood respiratory infections in childhood [ 42 ]; maternal BMI which may increase the risk of childhood infections [ 43 ]; or explore the potentially mediating effect of breastfeeding, which is known to be protective against certain infections during early childhood [ 7 , 8 ]. Finally, we only included births occurring in NHS hospitals as births occurring in private or military hospitals or at home were excluded due to poor linkage rates with hospital admission records.…”
Section: Discussionmentioning
confidence: 99%
“…Outcomes were largely grouped into 3 types of immune system–related conditions. The first included infective diseases, overall and by type-specific conditions (as outlined by Videholm et al 21 ). The second included conditions associated with an overactive immune system and inflammation, such as asthma, eczema, and allergies and anaphylaxis.…”
Section: Methodsmentioning
confidence: 99%
“…The International Statistical Classification of Diseases and Related Health Problems, Tenth Revision, Australian Modification was used to assign diagnoses for both the hospital and ED data. For infection, diagnoses were derived from Videholm et al, 21 while codes for autoimmune conditions were compiled from multiple published studies. 22 , 23 , 24 , 25 …”
Section: Methodsmentioning
confidence: 99%
“…For instance a study found a relatively low incidence of contacts general practitioners among Norwegian children [5]. Similarly, various Swedish studies indicated relatively low rates of different services such as hospitalisations for infection, outpatient contacts and antibiotics prescriptions compared to the level among Danish children [68]. On the other hand a study comparing use of antibiotic prescriptions among Swedish and Estonian children suggested that the Danish level was between that of these two countries respectively [9].…”
Section: Introductionmentioning
confidence: 99%